Processing of Anthropogenic Waste of Smelters of the Ural Mining and Metallurgical Company - Panshin, A.M.; Yakornov, S.A.; Skopov, G.V. (KnE Materials Science, 2020)
The industrial sites of the smelters of the Ural Mining and Metallurgical Company have accumulated a lot of anthropogenic waste, the processing of which is currently economically impractical. These primarily include tailings and beneficiation tailings, as well as waste granulated and copper smelting slag. This article conducts studies on technologies for x-ray-radiometric/magnetic separation enrichment of discard slags of MMSK as well as using jigging machines. Slag and slag enrichment tailings are used for cement production and road construction. For complex processing of fine copper smelting dusts OJSC Chelyabinsk zinc plant developed, tested and implemented a special technology. After implementation of ”Actions to process industrial waste generated by UMMC enterprises at metallurgical enterprises of UMMC-Holding Corp.”, the following were noted: concentrators and special beneficiation facilities process slag; R&D on complete processing of concentrator’s tailings was conducted; smelting dust was not stored but processed in full; the technology of implementing Waelz process for processing of steel smelting dust has been developed and commercially tested; the technology for extraction of copper and precious metals from pyrite dross is to be improved. Keywords: anthropogenic waste, dust, tailings, slag, pyrite dross